Teaching of preventive medicine in higher medical educational institutions of Ukraine in modern conditions - Kirsanova, O. V.; Кірсанова, Олена Валентинівна (My University, 2023)
The priority of the system of higher medical education is the training of highly competent and highly qualified specialists in medical universities. The modern pedagogical paradigm is based on the formation of professional competencies. The purpose of the work was to substantiate the system of formation of professional competences during the training of «Medicine» specialists in higher educational institutions. The materials for the research were the normative base of the educational process in the training of medical students and international experience in preventive medicine. The work uses methods: content analysis, system analysis, logical generalization, medical-statistical, Delphi. The main goal of a higher education institution is to train competent specialists who have significant health potential and are able to maintain professional activity at a high level for a long time. The system of formation of professional competencies in «Preventive Medicine» is aimed at logistical management of activities in the training process and ensuring the selectivity of health care management in medicine. The main special competencies include mastering the basic methods of protecting doctors from possible adverse working conditions; mastery of the basic methods of environmental protection; mastery of methods of complex formation of health with the help of pharmaceutical support and nutritional support of the body; ensuring the necessary level of individual safety in the event of the occurrence of typical dangerous situations or based on information about the predicted situation; the ability to carry out sanitary and hygienic and preventive measures. In modern military conditions, mastering the tactics of providing emergency medical aid and the ability to carry out medical and evacuation measures are of great importance. Пріоритетом системи вищої медичної освіти є підготовка в медичних університетах висококомпетентних і висококваліфікованих фахівців. Сучасна педагогічна парадигма базується на формуванні професійних компетенцій. Метою роботи було обґрунтування системи формування професійних компетенцій при підготовці у вищих навчальних закладах фахівців з «Медицини». Матеріалами для дослідження слугували нормативна база навчально-виховного процесу при підготовці студентів-медиків та міжнародний досвід з профілактичної медицини. У роботі використано методи: контент аналізу, системного аналізу, логічного узагальнення, медико-статистичний, Дельфійський. Головна мета вищого навчального закладу полягає у підготовці компетентних фахівців, які мають значний потенціал здоров’я та здатні довготривало підтримувати професійну діяльність на високому рівні. Система формування професійних компетенцій з «Профілактичної медицини» спрямована на логістичне управління заходами в процесі навчання та забезпечення селективності управління охорони здоров’я у медицині. До головних спеціальних компетентностей відноситься володіння основними методами захисту лікарів від можливих несприятливих умов праці; володіння основними методами збереження навколишнього середовища; володіння методами комплексного формування здоров’я за допомогою фармацевтичного супроводу і аліментарної підтримки організму; забезпечення необхідного рівня індивідуальної безпеки у разі виникнення типових небезпечних ситуацій або на основі інформації про прогнозовану ситуацію; здатність проведення санітарно-гігієнічних та профілактичних заходів. В сучасних військових умовах велике значення мають володіння тактикою надання екстреної медичної допомоги та здатність до проведення лікувально-евакуаційних заходів.
Викладання профілактичної медицини в вищих медичних навчальних закладах України в сучасних умовах
Kirsanova O. V. - 0000-0001-5337-2439
Keywords: professional competences; formation; students; preventive medicine; професійні компетенції; формування; студенти; профілактична медицина